Differences in platelet counts using venous blood and capillary blood for medical laboratory technology students at the Aisyiyah Pontianak Polytechnic - Khairul Bariyah; Paula Dwi Umiyah (Journal of Indonesian Medical Laboratory and Science, 2026)
Background: Platelets are blood cells that are important for the blood clotting process. Platelets make up most of the blood when blood vessels burst, bleed, or when the skin is torn and injured. In humans, platelets normally number between 150,000 - 400,000 per microliter of blood. Platelets are a very important component in the hemostasis response which is related to other hemostasis components Objectives: The aim of the research was to determine the difference in platelet count results using venous blood and capillary blood for students of the 'Aisyiyah Pontianak Polytechnic Medical Laboratory Technology Study Program Materials and Methods: The type of research method used is quantitative observational analytical research using a cross sectional approach research design. Purposive sampling research sampling. The sample population in the study consisted of 64 venous blood and 64 capillary blood from students Results: The results of the T-test statistical analysis of the difference in platelet count using venous blood and capillary blood found a p value of 0.000 where the T-test value, if the p value is 0.000 < 0.05, Conclusions: means that the conclusion is that there is a difference between the platelet count of venous blood and capillary blood. towards 'Aisyiyah Pontianak Polytechnic Medical Laboratory Technology students.